ANALISA METALURGI DAN SUPERVISIPERBAIKAN POROS FORCED DRAFTFAN SEBVAK UNIT PLTU - Adnyana, D. N. (MESIN, 2006)
Aforceddraftfan (FDF) shaft of a steam generatingpower plantfailed after several years inservice.Thefailed shaft showed a deep surface scratch on its one end and this was likely caused and advanced by thebearingfailure. The scratched endshaft was decided to repair by in-situ welding and machining. Anumber ofin-situ metallurgical examinations were performed to determine type ofmaterial and degree ofdamage thathave occurred on the shaft including: dye-penetrant test, chemical composition analysis, metallography byreplica technique and hardness test. From the test results obtained itwasfound that the FDFshaft was madeof material with specification ofJIS S45C or equivalent toAISI1045 - 1050. The test results obtained wereused to determine the machining depth being made onthe scratched shaft before performing welding repairand the welding process parameters required such as type of welding electrode and diameter, weldingcurrent, pre-heat temperature and post-weld heat treatment. The result of weld repair obtained showed thatthe hardness value of the repaired shaft was approximately close to the hardness value of the normal shaftmaterial, namelyrangedfrom 170 to 173 HB.